Navigating Digital Content Proliferation: A Study on the Information Behaviour of Communication Science Students at UINSU - Fahirah, Raisah; Ritonga, Muhammad Husni (Lafadz Jaya Publisher, 2024)
This study aims to understand the impact of digital content proliferation on the information consumption behaviour of Communication Science students at the State Islamic University of North Sumatra (UIN-SU). The development of information and communication technology has fundamentally changed the media landscape, shifting focus from conventional media to digital platforms such as social media, online news sites, and blogs. This phenomenon has broadened access to various types of content, challenging students to navigate, evaluate, and utilise information effectively. Amidst the increasing volume and diversity of information sources, Communication Science students, as adaptive and active technology users, often face challenges in distinguishing between accurate information and misinformation, which can significantly influence their opinion formation and behaviour. Adopting a qualitative methodology with a phenomenological approach, this study integrates the Uses and Effects analysis to deepen the understanding of how daily interactions with mass media affect students. Data was collected through in-depth interviews, observations, and documentation from March to May 2024, exploring how students select, process, and use digital information in their daily lives. The findings indicate that students tend to prioritise visual and interactive content but often get trapped in filter bubbles that affect their understanding and attitudes towards important issues. Therefore, this study highlights the need for more integrated media literacy education in the curriculum to equip students with the critical skills necessary to handle the complexity of information in the digital era. Further discussion of these findings is expected to provide valuable insights for the development of future educational and communication strategies.